FINANCIAL ANALYSIS OF PHARMACEUTICAL COMPANIES - E. Sedova; A. Chechulina (Вестник университета, 2019)
In the article the observed factors affecting the production of medicines, as well as indicate what documents regulating the activities of these enterprises. Identified the stages of financial analysis of pharmaceutical companies, described in detail techniques of financial analysis in pharmaceutical institutions and economic indicators that characterize all the economic activities of the pharmaceutical network.